جمالية الإيقاع في شعر ابن حريق البلنسي - شوية, محمد; معاش, حياة (جامعة الوادي - University of Eloued, 2021)
ملخَّـص: يُعتبرُ ابن حريق البَلنسي أحد كبار شعراء الأندلس في زمانه، إذ استطاع أنْ يَـنظِم قصائده في جُلِّ الأغراض الشِّعريًّة المعروفة، التزاماً بالقصيدة العربيّة العموديَّة ذات الأوزان الخليليّة، فكان أنْ نال بذلك مكانةً أدبيَّةً مرموقةً، ولُـقِّب بفحْل الشُّعراء! وجاءت الدِّراسات الـنَّقديَّة الحديثة فأعـطت بُعداً جديداً للنُّصوص الإبداعـيَّة، فصار لها تَـذوُّقٌ جديدٌ، ومن ذلك الدِّراسة الأسلوبيَّة التي تـدرسُ النَّصَّ في جوانبه الصَّوتيَّة والتَّركـيبيّة والبلاغـيَّة، فـتخوضَ في عُـمقه وتبرزُ جَـماليَّـته، وابن حريق البلنسي ضمَّن ذلك في نصوصه الإبداعيَّة الشِّعـريَّة، فكانتْ جَـمَالاً أثَّـر في المُتـلقِّي، وجعلته يعيشُ النصوص وكأنَّها قِــيلت السَّاعة. Abstract: Ibn Harik Al-Balansi was considered one of Andalusia’s greatest poets in his time. He was able to author his poems in most of the well-known poetic purposes, adhering to the vertical Arabic poem of Khalili weights, Which attained him a prestigious literary position, and He was called by the man of poets. Modern critical studies gave a new dimension to creative texts, so they had a new taste, such as stylistic study that covers the text in its phonemic, structural and rhetorical aspects, so it delves into its depth and embellishment in its aesthetics which is what Ibn Harik Al-Balansi included in his creative poetic texts, creating by that a sublime effect in the souls of the readers and making it live these poems as if it were in real life.
مقال
Keywords: المبدع ; المدحُ ; الإيقاع ; الوزن ; القافـيّة ; الصّوت